Pengaruh Model CORE Berbantuan Qreatif.id terhadap Pemahaman Konsep Rantai Makanan Siswa Kelas V SD - Nur’aina Nur’aina; Sarah Fazilla; Rosimanidar Rosimanidar (YASIN, 2026)
The limited number of studies on the implementation of cooperative learning models integrated with digital media indicates the need for learning innovations that can improve students’ conceptual understanding in IPAS learning in elementary schools. This study aimed to analyze the effect of the CORE (Connecting, Organizing, Reflecting, Extending) cooperative learning model assisted by the Qreatif.id application on students’ understanding of the food chain concept. This study used a quantitative approach with a quasi-experimental design, involving 32 students selected using simple random sampling. Data were collected using test instruments in the form of pretests and posttests, and were then analyzed through the N-Gain test and t-test with the assistance of SPSS. The results showed a significant increase in students’ conceptual understanding, as indicated by higher posttest and N-Gain scores in the experimental class than in the control class. This finding reinforces the relevance of constructivist theory in learning, particularly through students’ active involvement in connecting, organizing, reflecting on, and extending the concepts learned. Thus, the CORE cooperative learning model assisted by the Qreatif.id application plays an important role in improving elementary school students’ understanding of the food chain concept. The implications of this study include theoretical contributions to the development of constructivist-based learning models and practical recommendations for teachers to utilize interactive digital media in the IPAS learning process.